How to make arguments based on legal consequences? Definition of its scope and uses - Velásquez Meléndez, Raffo (2020)
The argumentation based on consequences is used in daily life. However, the legal field, it has to accomplish some requisites to be admissible. Thus, the purpose of this article is define what kind of reasoning by consequences can be used in the legal field. For this, it will be presented where the argumentation works, the ways of presenting it, scenarios in which it is not admissible and, finally, the types of consequences that can rightfully be invoked.